2008
DOI: 10.1016/j.exer.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

IGF-II is present in bovine corneal stroma and activates keratocytes to proliferate in vitro

Abstract: Extracts of bovine corneal stroma have been shown to activate keratocytes in culture to proliferate. We fractionated stromal extract on a column of Sephacryl S-300 and tested the fractions for mitogenic activity using cell culture and for the presence of IGF-II and its binding protein IGFBP-2 by Western blot. We found that the mitogenic activity in the extract separated into major and minor peaks and that immunologically detectable IGF-II and IGFBP-2 co-eluted with the minor peak. We also compared the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…High expression levels of IGF-2 were observed also immunohistochemically and at mRNA level in tumor and in stromal cells (Nosho et al 2005;Sayer et al 2005;Diehl et al 2006;Kornprat et al 2006;Pavelic et al 2007;Weber et al 2007). While IGF-2 is important for normal epithelial cells, it is also able to stimulate proliferation of tumor cells (Brady et al 2007;Musselmann et al 2008). We observed the positive effect of SCCF on epithelial-mesenchymal transition (Lacina et al 2007a), and this phenomenon seems to be positively controlled by IGF-2 (Arciniegas et al 2006).…”
Section: Discussionmentioning
confidence: 59%
“…High expression levels of IGF-2 were observed also immunohistochemically and at mRNA level in tumor and in stromal cells (Nosho et al 2005;Sayer et al 2005;Diehl et al 2006;Kornprat et al 2006;Pavelic et al 2007;Weber et al 2007). While IGF-2 is important for normal epithelial cells, it is also able to stimulate proliferation of tumor cells (Brady et al 2007;Musselmann et al 2008). We observed the positive effect of SCCF on epithelial-mesenchymal transition (Lacina et al 2007a), and this phenomenon seems to be positively controlled by IGF-2 (Arciniegas et al 2006).…”
Section: Discussionmentioning
confidence: 59%
“…Gpc functions may be mediated via IGF-II, and Igf2 was elevated in P10 corneas (Supplemental Table 1). A recent study also reported IGF-II in the bovine cornea and its role in regulating stromal keratocyte proliferation (Musselmann et al 2008). Igfbp2, encoding an IGF binding protein that modulates IGF levels and its autocrine and paracrine functions was also found to be over expressed in the cornea of both ages by microarray and RT-PCR.…”
Section: Discussionmentioning
confidence: 98%
“…High levels of insulin would not normally be present in the corneal stroma, however IGF-II, another ligand for IGF-IR, is in the bovine corneal stroma and it causes bovine keratocytes to proliferate and maintain their normal phenotype in vitro (Musselmann et al 2008). IGF-I has previously been shown to stimulate the proliferation of rabbit keratocytes in vitro while maintaining their dendritic morphology (Jester and Ho-Chang 2003).…”
Section: Introductionmentioning
confidence: 99%